Pre or perioperative period: when is the best time to produce platelet-rich plasma in dogs? - Aleixo, Grazielle Anahy de Sousa; Coelho, Maria Cristina de Oliveira; Teixeira, Miriam Nogueira; Andrade, Lilian Sabrina Silvestre; Cunha Paranhos de Oliveira, Maria Clara; Maia, Flávia Corrêa; Bessa, Ana Luiza Neves Guimarães; Evêncio-Neto, Joaquim; Mesquita, Emanuela Polimeni (Medicina Veterinária, 2022)
Published studies about production of platelet-rich plasma (PRP), demonstrate differences related to the moment in when blood should be collected and processed. Blood collection could be performed before surgery, prior to the administration of drugs, fluids, or any surgical trauma, while others collect blood during the perioperative period. The present objective was to determine if blood collection and processing in the pre or perioperative periods would result in different platelet concentrations, and consequently, what period is recommended to prepare a best PRP. Blood samples were obtained from 20 healthy female dogs at two distinct moments: before surgery, prior to the administration of drugs and fluids (M0), and later, in the operation room, after administration of anesthetics and intravenous fluids (M1). To obtain PRP, blood was centrifuged at 1200 rpm for ten minutes, then at 1600 rpm for ten minutes. Results showed that blood collected at M1 had a 29% decrease in platelet count compared to M0 (highly significant statistical difference), what interferes directly in PRP quality, and therefore, it is concluded that blood collection and PRP processing should be realized at M0.